Peran Perempuan dalam Pengembangan Wakaf di Persyarikatan Muhammadiyah DIY - Sari, Fitria Nurma; Rohman, Hilma Fanniar (ITB AAS Indonesia Surakarta, 2024)
The main contribution of this research is to reveal the fundamental factors that influence women's intentions in distributing their waqf through the Muhammadiyah organization. The strong reason this research was carried out was because of the potential of waqf assets that could still be optimized to improve social welfare, economic empowerment and infrastructure development. If the biggest influencing factor for a person, especially women, in distributing waqf in the Muhammadiyah organization can be researched, it will be able to help the Muhammadiyah Association and similar organizations to better understand the role of women, especially in the aspect of waqf development, and design more inclusive strategies to encourage greater women's participation. in future waqf activities. The type of research used is field research with quantitative research methods. The data used is primary data using a questionnaire technique which was distributed to 30 female wakif respondents who had the intention to donate to the DIY Muhammadiyah Association. The number of variables studied is 7 variables, which are the dependent variables, namely understanding of waqf products, religiosity, transparency of financial reports, reputation of the Institution, ease of access, loyalty as a member as well as the variable interest in waqf as the independent variable. The sampling method in this research used a sampling technique, namely purposive sampling of female waqifs who were members of the Muhammadiyah DIY organization. The analysis method uses descriptive statistics and inferential statistics as well as multiple linear regression analysis with SPSS 26.0 software. The results of this research show that the variables influencing understanding of waqf products, religiosity, transparency of financial reports, reputation of the institution, program innovation, ease of access, and aspects loyalty as a member have a significant effect on interest in waqf with a significance value of 0.030 which is smaller than the significance used. namely 0.05 or 5%. Partially, the variables understanding waqf products, religiosity, ease of access, and the variable loyalty as a member have a significant effect on interest in waqf, while other variables such as transparency of financial reports, and institutional reputation variables do not have a significant effect on interest in waqf.